Characterization and application of monoclonal antibodies against porcine epidemic diarrhea virus - Wang, Yin (Kansas State University, 2015)
Porcine epidemic diarrhea virus (PEDV) causes acute diarrhea to pigs at all ages, resulting in high mortality rate of 80-100% in piglets less than one week old. Within one year after the outbreak in April 2013, PEDV has rapidly spread in the US and causes the loss of over 10% of the US pig population. Monoclonal antibody (mAb) is a key reagent for rapid diagnosis of PEDV infection. In this study, we produced a panel of mAbs against nonstructural protein 8 (nsp8), spike(S) protein, and nucleocapsid (N) protein of PEDV. Four mAbs were selected, which can be used in various diagnostic assays, including indirect immunofluorescence assay (IFA), enzyme-linked immunoabsorbent assay (ELISA), Western Blot, immunoprecipitation (IP), immunohistochemistry (IHC) test and fluorescence in situ hybridization (FISH). The mAb 51-79 recognizes amino acid (aa) 33-60 of nsp8, mAb 70-100 recognizes aa1371-1377 of S2 protein, and mAb 66-155 recognizes aa 241-360 of N protein, while mAb 13-519 is conformational. Using the mAb70-100, the immunoprecipitated S2 fragment was examined by protein N-terminal sequencing, and cleavage sites between S1 and S2 was identified. In addition, this panel of mAbs was further applied to determine the infection site of PEDV in the pig intestine. IHC test result showed that PEDV mainly located at the mid jejunum, distal jejunum and ileum. Results from this study demonstrated that this panel of mAbs provides a useful tool for PEDV diagnostics and pathogenesis studies.
Keywords: Porcine epidemic diarrhea virus; monoclonal antibody characterization; monoclonal antibody production; Virology (0720)